Creating and Disseminating Knowledge Among Organizational Scholars: The Role of Special Issues - Olk, Paul; Griffith, Terri L. (Organization Science, 2004)
Special issues of scholarly journals have become more common during the last decade of management research. We review this trend and assess the effectiveness of special issues for knowledge dissemination. Methods include interviews with journal editors, compiling data on time to publication and on impact and quality of special issues for five mainstream management journals, and a case study chronicling the creation of the Organization Science special issue on “Knowledge, Knowing, and Organizations.” The findings show that journal special issue articles appear to be published more quickly than regular issue articles (time to publication), and for three of the five journals there is a significant difference in impact (measured as citation counts per article) when special and regular issue articles are compared. Further, we find evidence of greater variation in the quality of special issue articles compared to regular issue articles, although this reflects special issues publishing exceptional articles rather than the inclusion of substandard ones. The case analysis suggests that a series of preconferences on a common topic prior to a special issue did not appear to impact the type of papers submitted to or published in the special issue. We discuss the role of special issues and preconferences in knowledge development in organization science.